The influence of corporate governance on the performance of public companies included in the CGPI rating for the 2005-2007 period - Irma Yohana (Indonesia Auditing Research Journal, 2022)
The purpose of this research is to investigate the influence of corporate governance implementation on firm performance. The samples of this research is non financial public companies which include the CGPI rating in 2005, 2006 and 2007. The dependent variable are ROE and Tobin’s Q as operating and market performance. Independent variable of this research is corporate governance perception index and this study uses leverage and firm size as control variables. This study use 34 objects that meet some criteria. Using multiple regression analysis, this research found that corporate governance implementation has a positive significant influence to ROE as operating performance and also found that corporate governance implementation has a positive significant influence to Tobin’s Q as market Performance.